Evidence of the genetic and spatial structure of Nasua narica in Central America and northern South America from mitogenomic analysis - Jaramillo, María Fernanda; Ruiz-García, Manuel (THERYA, 2022)
Carnivores are extremely important in ecosystem dynamics. Coatis (Procyonidae) are a group of Neotropical species with highly developed social behavior. One coati species is the Central American or white-nosed coati (Nasua narica). This work describes the analysis of two sets of mitochondrial data for a sample of N. narica covering most of the geographic distribution range of the species. The first data set analyzed 74 specimens for three mitochondrial loci; the second, 59 specimens for complete mitochondrial genomes. Our phylogenetic analyses revealed six distinct genetic groups of N. narica in southern México, Central America, and South America, which, together with three additional groups found in northern México and southern USA in a previous study, resulted in a total of nine genetically distinct groups of N. narica. The first genetic group (G1), which began to differentiate 4.1 to 3.2 million years ago, was located on the Pacific coast of Ecuador and northern Colombia. A second genetic group (G6) was detected in northern Colombia, Panama, and southern Costa Rica, being introgressed by mitochondrial DNA from the mountain coati (Nasuella olivacea). The third genetic group (G3) was located in Costa Rica, Nicaragua, El Salvador, Honduras, and southern Guatemala. The fourth genetic group (G4) was located in north-central Guatemala and Belize. The fifth genetic group (G5) was distributed in southern México (Chiapas, Tabasco, Campeche, Quintana Roo, and Yucatán) and northern Guatemala. Finally, the sixth genetic group (G2) was found only in Mérida (Yucatán, México). Groups G2 to G5 became mitochondrially diversified over 1.9 to 1.1 million years. All groups showed high mitochondrial genetic diversity, although the South American genetic group (G1) had the highest diversity. The northern genetic groups (G4, G5) had lower genetic diversity, except for the Merida group, which is likely composed of other undetected subgroups. The existence of six (nine, considering another study) well-developed groups in N. narica is related to female phylopatry and climatic changes during the Pleistocene. A spatial autocorrelation analysis showed a very high structure, well in line with the south-to-north colonization of the American continent by N. narica.